Prevalence of Asymptomatic Uterine Leiomyoma in Western Turkey and Factors Affecting Myoma Presence - Tasgoz, Fatma Nurgul; Kender Erturk, Nergis (Gynecology Obstetrics & Reproductive Medicine, 2022)
Objective: To reveal the prevalence of asymptomatic uterine leiomyomas among gynecologic patients and to evaluate risk factors associated with the presence of leiomyomas. Study Design:Two thousand five hundred eighty-three patients aged between 18 and 66 years who presented to the gynecology outpatient clinic of our hospital in January and February 2021 who had an intact uterus and underwent transvaginal ultrasound were included in the study. Patients withsymptoms due to fibroids were defined as symptomatic, and those without symptomswere defined as asymptomatic; then two groups were compared in terms of certain variables.The independent risk factors associated with the presence of fibroids were determined using univariate and multivariate logistic regression analysis. Results: Leiomyomas were detected in a total of 437 patients with an overall prevalence of 17.2%. Leiomyomas were detected in 12.2% of asymptomatic patients and 27.8% of symptomatic patients (p<0.001). The prevalence of fibroids tended to increase with advancing age and decreased after age 50 years. It was observed that myoma diameter was significantly large (29.5 (6-123) mm and 18 (7-74) mm; p<0.001) and the frequency of multiple myomas was significantly high in symptomatic patients (46.5% vs. 33.6%; p<0.001). In the multivariate logistic regression analysis, high body mass index, younger age at menarche, and not using oral contraceptives were associated with the presence of fibroids. Conclusion: Approximately half of all leiomyomas, one of the important gynecological health problems of women, are asymptomatic.